Vitamin D supplementation of 4000 IU daily and cardiac function in patients with advanced heart failure: The EVITA trial. (1st April 2019) - Zittermann, A.; Ernst, J.B.; Prokop, S.; Fuchs, U.; Gruszka, A.; Dreier, J.; Kuhn, J.; Knabbe, C.; Berthold, H.K.; Gouni-Berthold, I.; Pilz, S.; Gummert, J.F.; et al.
Abstract: Background: Data regarding the effects of vitamin D on cardiac function are inconclusive. Methods: In a post-hoc analysis of the EVITA (Effect of vitamin D on mortality in heart failure) trial, we investigated whether a daily vitamin D3 supplement of 4000 IU for three years affects echocardiography parameters like left ventricular end-diastolic diameter (LVEDD), LV end-systolic diameter (LVESD), and LV ejection fraction (LVEF) in patients with advanced heart failure (HF) and 25‑hydroxyvitamin D levels <75 nmol/L. Of 400 patients enrolled, 199 were assigned to vitamin D and 201 to placebo. We assessed time × treatment interaction effects using linear mixed models and analyzed in subgroups vitamin D effects at 12 and 36 months post-randomization using analysis of covariance with adjustments for baseline values. Results: At baseline, values of LVEDD, LVESD, and LVEF were 67.5 ± 10.5 mm, 58.9 ± 12.0 mm, and 30.47 ± 10.2%, respectively. There were no time × treatment interaction effects on LV echocardiographic parameters in the entire study cohort, neither at 12 months nor at 36 months post-randomization (P-values > 0.05). However, in the subgroup of patients aged ≥50 years, vitamin D treatment was associated with an increase in LVEF of 2.73% (95%CI: 0.14 to 5.31%) at 12 months post-randomization (n = 311). The increase was slightly attenuated to 2.60% (95%CI: −2.47 to 7.67%) at 36 months post-randomization (n = 242). Conclusion: Our data indicate that vitamin D supplementation does not significantly improve cardiac function in all patients with advanced HF. However, vitamin D probably improves LV function in HF patients aged ≥50 years. Highlights: The effect of vitamin D on cardiac function is hotly debated but available data are inconclusive. We investigated the effect of a daily vitamin D3 supplement of 4, 000 IU for three years on cardiac function. Vitamin D supplementation may not improve cardiac function in all patients with heart failure, but probably in patients aged ≥ 50 years.